Firm Value: Profitability, Leverage, and Firm Size with Corporate Social Responsibility (CSR) as A Moderating Variable - Elsa Monica; Wyndha Zahra Desanti; Rawi (Rescollacom (Research Collaborations Community), 2025)
This study aims to examine the effect of Profitability, Leverage, and Firm Size on Firm Value with Corporate Social Responsibility (CSR) as a moderating variable. In the era of globalization and increasing competition, companies are not only expected to achieve financial gains but also to take broader social and environmental responsibilities into account. The sample used in this study consists of 100 companies listed on the LQ45 Index of the Indonesia Stock Exchange during the 2020 to 2023 period.The analytical method used in this research is multiple linear regression analysis with a moderating approach. The findings indicate that Profitability and Firm Size have a positive effect on Firm Value, while Leverage has a negative effect. Furthermore, Corporate Social Responsibility (CSR) is proven to function as a moderating variable that strengthens the influence of Profitability, Leverage, and Firm Size on Firm Value. These results provide valuable insights for company management in optimizing firm value through effective management of Profitability, Leverage, Firm Size, and CSR. This study is expected to make a significant contribution to the development of corporate finance literature and serve as a useful guide for investors in making investment decisions.